2022
DOI: 10.1093/bib/bbac074
|View full text |Cite
|
Sign up to set email alerts
|

MutateX: an automated pipeline for in silico saturation mutagenesis of protein structures and structural ensembles

Abstract: Mutations, which result in amino acid substitutions, influence the stability of proteins and their binding to biomolecules. A molecular understanding of the effects of protein mutations is both of biotechnological and medical relevance. Empirical free energy functions that quickly estimate the free energy change upon mutation (ΔΔG) can be exploited for systematic screenings of proteins and protein complexes. In silico saturation mutagenesis can guide the design of new experiments or rationalize the consequence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 100 publications
0
32
0
Order By: Relevance
“…We have used an in silico mutational scan based on MutateX [ 46 ] and the FoldX energy function [ 47 ] to investigate whether AMBRA1 mutations validated for this study were likely to affect the stability of the β-propeller domain (Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have used an in silico mutational scan based on MutateX [ 46 ] and the FoldX energy function [ 47 ] to investigate whether AMBRA1 mutations validated for this study were likely to affect the stability of the β-propeller domain (Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we included residues proposed to be involved in the binding of 2-oxoglutarate. 19 We complemented the FuncLib scans with in silico saturation mutagenesis using MutateX, an automated pipeline 22 based on the FoldX energy function. 21 It has been shown that FoldX is effective in predicting destabilizing mutations in proteins.…”
Section: Resultsmentioning
confidence: 99%
“…We employed the FoldX energy function 21 to perform in silico saturation mutagenesis using MutateX, an automated pipeline that we recently developed. 22 Thus, we employed the same protocol we had applied to other proteins 29 , 30 to estimate the changes caused by the selected mutations on the structural stability of Hgdh. To this end, we performed the calculations on a monomer derived from the X-ray structure of Hgdh (PDB ID 1XDW , monomer in chain A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…-Biophysical effects of mutations: FoldX version 5.0 (56, 57) was used with the MutateX wrapper (58) to simulate all possible mutations on the biological assembly of DfrB1 (PDB: 2RK1).…”
Section: 32-random Forest Regressormentioning
confidence: 99%